Deletion of the rodent malaria ortholog for falcipain-1 highlights differences between hepatic and blood stage merozoites - Hopp, Christine S. (2017)
:© 2017 Hopp et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.